Employment transitions for spouses of stroke survivors: evidence from Swedish national registries - Josefine Persson; Gunnel Hensing; Carl Bonander (BMC, 2020)
Abstract Background The sudden occurrence of stroke often leads to impaired physical, emotional, and cognitive abilities. Many stroke survivors therefore require support from their family members. However, little is known about the effects of a stroke event on the spouses' employment transition probabilities. The aim of this study was twofold 1) to investigate whether a first ever stroke has an effect on employment transition probabilities for employed and unemployed spouses and 2) to analyze whether heterogeneity with respect to age, gender, education and comorbidities influence the size of the effect. Method Data for this population-based cohort study were extracted from Swedish national registries from 2005 to 2016. The national sample consisted of 1818 spouses of first ever stroke survivors during 2010 and 2011, and 7399 matched controls that were employed or unemployed during 5 years prior stroke onset. Effects of stroke on spousal employment transitions were analyzed using linear regression, stratified by employment status prior to stroke onset. Results Employed spouses prior stroke onset reduced their employment by − 1.3 percentage points (95% CI, − 2.4, − 0.2). The data also indicated that employed spouses with lower age, comorbid conditions, and low educational attainment may be at even greater risk of transitioning to unemployment. On the other hand, stroke events appear to have limited impact on spouses that were unemployed prior to stroke onset. Conclusion The risk of transitioning to unemployment appears to increase after stroke onset for spouses of stroke survivors, and disadvantaged groups may be at even greater risk. Thus, it is important for policy-makers to implement interventions to ensure that these groups of spouses have the possibilities to combine their caregiving role and remaining in the labor market.